2009
DOI: 10.5194/acp-9-3209-2009
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous reaction of hydroxyl radicals with sub-micron squalane particles: a model system for understanding the oxidative aging of ambient aerosols

Abstract: Abstract. The heterogeneous reaction of OH radicals with sub-micron squalane particles, in the presence of O 2 , is used as a model system to explore the fundamental chemical mechanisms that control the oxidative aging of organic aerosols in the atmosphere. Detailed kinetic measurements combined with elemental mass spectrometric analysis reveal that the reaction proceeds sequentially by adding an average of one oxygenated functional group per reactive loss of squalane. The reactive uptake coefficient of OH wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
242
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(263 citation statements)
references
References 40 publications
18
242
3
Order By: Relevance
“…Since the concept of potential aerosol mass (PAM) was proposed, the PAM reactor, operated as a flow tube reactor, has been widely used in laboratory and field studies of SOA formation (Chen et al, 2013;Kang et al, 2007Kang et al, , 2011Keller and Burtscher, 2012;Kroll et al, 2009;Lambe et al, 2011aLambe et al, , 2012Lambe et al, , 2015Ortega et al, 2016Ortega et al, , 2013Palm et al, 2016;Slowik et al, 2012;Smith et al, 2009). A powerful attribute of the PAM and subsequent flow reactors is the capability to generate hydroxyl radical (OH) levels that lead to integrated OH exposure ranging as high as ∼ 10 12 molecules cm −3 s, at which it is possible to simulate atmospheric oxidation conditions comparable to those occurring over ∼ 1 week.…”
Section: Y Huang Et Al: the Caltech Photooxidation Flow Tube Reactormentioning
confidence: 99%
“…Since the concept of potential aerosol mass (PAM) was proposed, the PAM reactor, operated as a flow tube reactor, has been widely used in laboratory and field studies of SOA formation (Chen et al, 2013;Kang et al, 2007Kang et al, , 2011Keller and Burtscher, 2012;Kroll et al, 2009;Lambe et al, 2011aLambe et al, , 2012Lambe et al, , 2015Ortega et al, 2016Ortega et al, , 2013Palm et al, 2016;Slowik et al, 2012;Smith et al, 2009). A powerful attribute of the PAM and subsequent flow reactors is the capability to generate hydroxyl radical (OH) levels that lead to integrated OH exposure ranging as high as ∼ 10 12 molecules cm −3 s, at which it is possible to simulate atmospheric oxidation conditions comparable to those occurring over ∼ 1 week.…”
Section: Y Huang Et Al: the Caltech Photooxidation Flow Tube Reactormentioning
confidence: 99%
“…For example, the heterogeneous OH oxidation of insoluble or sparingly soluble organic compounds (e.g., squalane and bis(2-ethylhexyl)sebacate) produces water-soluble reaction products that enhance the CCN activity of corresponding aerosols (George et al, 2009;Harmon et al, 2013). A recent study has suggested that low-temperature OH oxidation may increase CCN activity of amorphous solid organic particles (Slade et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While flow tube reactors have been used to study the chemistry of inorganic particles since the 1950s (Robbins and Cadle, 1958;Hanson and Lovejoy, 1995), their application to the study of organic surfaces (Cooper and Abbatt, 1996;de Gouw and Lovejoy, 1998;Bertram et al, 2001) and organic particles (Morris et al, 2002;Katrib et al, 2005;Hearn and Smith, 2006; Published by Copernicus Publications on behalf of the European Geosciences Union. McNeill et al, 2008;Smith et al, 2009) is relatively recent.…”
Section: Introductionmentioning
confidence: 99%